O professor coordenador emergente da Proposta Curricular do Estado de São Paulo (gestão 2007-2010) - Freitas, Silvana Alves (2011)
This research aims at grasping the sense of emergence of a coordinating teacher based on the scanning of the Curricular Proposition in the State of São Paulo (2007-2010 Administration), which has been done through the analysis of the speech within documents on and to the coordinating teacher herein studied. This canvassing is grounded on the following questions: What kind of coordinating teachers emerge from the analysis of the Curricular Proposition in the State of São Paulo? Why have the coordinating teachers been elected as the foundation structure of this Proposition? In order to answer those inquiries, documental research has been used, having as sources the current laws on management standardization of the curriculum and literature provided by the São Paulo Department of Educational Affairs SEE/SP (which is aimed at guiding the pedagogical coordinating teachers, named Manager Booklets), in addition to a video lecture presented at the training course offered to coordinating teachers, which is available on the SEE/SP s website. The subject-matter analysis is based on the theory lines of Apple (2006) and Ponce (2009) with respect to the prescribed curriculum and its implications concerning ideology and power; the works of Mate (2009) and Fusari (2009) are considered with respect to the study on the coordinating teacher; and Franco (2008), Pimenta (2006) and Libâneo (2006) are considered with respect to the pedagogical education